Teaching accounting reform - ตฤณขจี, สุนีย์ (Business Administration and Management Journal Review, 2016)
Generally, accountancy curriculum objectives are to teach and train accountants to prepare data and document then inform the result. The requirement of accounting students are to study an introductory course that emphasizes only on analysis skill from assumption transactions. This leads to the problems after those students graduated and get job. For example, they cannot determine whether each voucher is the accounting transaction that related to business or not. As a result, it is the important duty of lecturers to train students to be familiar with practical and realistic works. The subject modules should be cover all problematic provided. The students will be qualifying roused to solve the question. Furthermore, it is necessary to target definite goals and what students will be able to do in order to modernize the accounting education path.